2013
DOI: 10.1158/1541-7786.mcr-13-0003-t
|View full text |Cite
|
Sign up to set email alerts
|

Fer Protein-Tyrosine Kinase Promotes Lung Adenocarcinoma Cell Invasion and Tumor Metastasis

Abstract: Epidermal growth factor receptor (EGFR) is frequently amplified or mutated in non–small cell lung cancer (NSCLC). Although Fer protein-tyrosine kinase signals downstream of EGFR, its role in NSCLC tumor progression has not been reported. Here, Fer kinase was elevated in NSCLC tumors compared to normal lung epithelium. EGFR signaling in NSCLC cells fosters rapid Fer activation and increased localization to lamellipodia. Stable silencing of Fer in H1299 lung adenocarcinoma cells (Fer KD) caused impaired EGFR-ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Increased Fer expression in RCC cells has previously been demonstrated to be positively associated with tumor growth and progression in patients with RCC (6). A similar phenomenon has been reported in other malignancies, including breast and lung cancer (16,26). However, the association between stromal Fer expression, tumor malignancy and survival remains to be elucidated.…”
Section: Stromal Fer Expression -------------------------------------supporting
confidence: 78%
“…Increased Fer expression in RCC cells has previously been demonstrated to be positively associated with tumor growth and progression in patients with RCC (6). A similar phenomenon has been reported in other malignancies, including breast and lung cancer (16,26). However, the association between stromal Fer expression, tumor malignancy and survival remains to be elucidated.…”
Section: Stromal Fer Expression -------------------------------------supporting
confidence: 78%
“…For example, the requirement of Fer for the deregulated proliferation of cancer cells in vitro is most profoundly manifested when the cells are grown in agarose under nonanchoring conditions accompanied by restricted nutrient and oxygen availability (51). Furthermore, shRNA knockdown studies carried out with mouse xenografts models showed that Fer plays an important role during the initiation of primary tumors (51) and is essential for the development of secondary metastases (26,27). This might reflect, at least in part, a required contribution of Fer to the initiation and early stages of tumor formation, during which the nutrient and oxygen supplying vasculature has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase was detected in all human malignant cell lines analyzed (20,21), and its levels in malignant prostate tumors are significantly higher than those detected in benign growths (22). Furthermore, downregulation of Fer impairs the proliferation of prostate, breast, and colon carcinoma cells (23), induces death in colon carcinoma and non-small cell lung cancer (NSCLC) cells (24,25), abolishes the ability of prostate carcinoma PC3 and V-Sis-transformed cells to form colonies in soft agar (22), and prevents the metastatic spread of breast and lung adenocarcinoma tumors (26,27). At the clinical level, high Fer expression levels have been linked to poor prognosis of hepatocellular carcinoma (HCC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive cancer cells take advantage of these processes during cancer cell invasion and tumor metastasis (38). This study adds to a growing list of membrane shaping BAR proteins that have been implicated in cancer metastasis (14,15,19,22,39,40). Through stable silencing of Endo II in TNBC cell models, we provide evidence that Endo II promotes internalization of EGFR and downstream signaling to Erk and Akt pathways.…”
Section: Discussionmentioning
confidence: 70%
“…BAR proteins both sense and promote membrane curvature via their BAR domains, and recruit key regulators of endocytosis and actin polymerization to these membranes via their SH3 domains (12,13). Indeed, several BAR proteins have been implicated in regulating cell motility, invasion, and metastasis in EGFR-driven cancer models (14)(15)(16)(17)(18)(19). Another BAR protein of potential relevance to metastatic TNBC is Endophilin A2 (hereafter called Endo II).…”
Section: Introductionmentioning
confidence: 99%